Study on Clinical Profile and Impact of Septoplasty in Patients Attending National Medical College Birgunj for Deviated Nasal Septum - Rain, MD Kamaluddin; Pradhan, Ram Kumar; Dhungana, Inclub (Med Phoenix, 2022)
Introduction: A deviated nasal septum is a common anatomic disorder that presents in up to 62% of the population but, not all are symptomatic. However, it may play a critical role in nasal obstruction symptoms, aesthetic appearance of the nose, increased nasal resistance and sometimes snoring. This study was done with an aim to determine the profile of subjects having deviated nasal septum and assess the impact of septoplasty on them. Materials and Methods: A cross-sectional study was done at National Medical College, Department of Otorhinolaryngology, Head and Neck Surgery, Birgunj from January 2022 to June 2022. Total 30 cases with symptomatic deviated nasal septum were included. Ethical clearance (F-NMC/579/078-79) was obtained from institutional review committee of NMC Birgunj. Details of nasal patency test followed by anterior rhinoscopy and nasal endoscopy were noted. Patients were followed up on 1st, 7th and 30th day post operatively after septoplasty. Pre and post operative comparison was done by using NOSE questionnaire. Wilcoxon signed rank test was done. Results: The ratio of male to female being 1.1:1. The age of the patients varied between 18 to 55 years, and the mean age was 29.07±10.409 years. most common type of deviation seen was type IV (30%). Nasal obstruction was seen in all the study cases which was followed by headache (76.7%) There was decline in the Nose scoring gradually from preoperative period to postoperative period. In anterior rhinoscopy spur (73.3%) was the most common finding. A significant (p<0.001) improvement in nose score after septoplasty was seen. Conclusion: Significant improvement in NOSE score was seen in our study which was in accordance with similar studies conducted.